Zebrafish neurobehavioral phenomics applied as the behavioral warning methods for fingerprinting endocrine disrupting effect by lead exposure at environmentally relevant level. (September 2019) - Li, Xiang; Zhang, Baoyue; Li, Ning; Ji, Xiuna; Liu, Kechun; Jin, Meng
Abstract: Environmental lead (Pb) exposure is a great hazard to the public health. Although environmentally relevant Pb poisoning is preventable, insidious Pb contaminants are still a major threat to human health. Herein, we reported that exposure to Pb at environmentally relevant concentration level (1 μg/L, 10 μg/L and 100 μg/L), disturbed the courtship behavior of adult male zebrafish and further altered the transcriptional patterns of key genes involved in testicular steroidogenesis ( igf3, amh, piwil1, lhcgr, fshr, cyp11c1, star, cyp19a1a, cyp19a1b ) and apoptosis ( bax, cytoC, caspase 9, caspase 3, puma ). Both the behavioral and the transcriptional profiles share a similar biphasic dose response, with stimulatory effects after low-level exposure and inhibitory effects after high-level exposure. This results revealed the endocrine disrupting effects of Pb even at an environmentally relevant level within the concentration range of ambient water quality criteria (AWQC) and the reliability of locomotion fingerprint as the indicator for detecting the risk induced by Pb pollution. Current research, for the first time, employed the ZebraTower system as the biological early warning system (BEWS) to find that Pb exerted biphasic effects on the courtship behavior and endocrine regulation of male adult zebrafish. Methodologically, we firstly propose an efficient solution to monitor and assess the risk of Pb exposure by combining the (BEWS) and data analyzing methods such as zebrafish phenomics, which would make a contribution to the detection and prevention of environmentally relevant Pb poisoning. Highlights: Pb of environmentally relevant concentration are of potential reproductive toxicity. Pb disturbed expression of genes involved in testicular steroidogenesis and apoptosis. Pb exerted biphasic effects on courtship behavior and endocrine regulation in male.